Non-invasive brain stimulation for treating catatonia: a systematic review - Xiao, Hongqi; Meng, Yajing; Liu, Shiyu; Cao, Yuan; Sun, Huan; Deng, Gaoju; Wang, Mei; Zheng, Yaozong; Qiu, Changjian (Frontiers in Psychiatry, 2023)
Background: Noninvasive brain stimulation (NIBS) techniques offer new therapeutic options for modifying pathological neuroplasticity and have been proven to be beneficial in the treatment of neuropsychiatric disorders. Objective: This study aimed to investigate the role of NIBS in treating catatonia. Materials and methods: We conducted a systematic search to identify meta-analyses or systematic reviews on electroconvulsive therapy (ECT) as well as studies on the effects of repetitive transcranial magnetic stimulation (rTMS) and transcranial direct current stimulation (tDCS) on patients with catatonia from the PubMed, Web of Science, Embase, China National Knowledge Internet, WanFang and China Science and Technology Journal databases from inception until July 31, 2022. The methodological quality of the included studies was assessed with the AMSTAR2 or Joanna Briggs Institute Critical Appraisal tools. Paired t-tests and Wilcoxon signed-rank tests were used to compare changes in catatonia symptom scores after rTMS or tDCS. Results: Thirteen systematic reviews and one meta-analysis on ECT, two systematic reviews and twelve case reports on rTMS, and seven studies of fourteen cases applying tDCS were identified. Systematic reviews of ECT consistently described improvement in catatonia symptoms across catatonia types and patient age groups. After treatment with rTMS (t=4.489, p=0.006) and tDCS (z=-3.065, p=0.002), patients exhibited significant improvement. Conclusions: ECT, rTMS, and tDCS were effective in treating catatonia. Early intervention with NIBS techniques may help improve catatonia symptoms in patients with schizophrenia. It may be advantageous to use rTMS or tDCS to maintain this improvement. NIBS techniques may thus represent a promising treatment for catatonia, but additional high-quality randomized controlled trials are needed.